The formation of the professionals for the timber industrial sector of the civil construction - Bittencourt, Rosa Maria [UNESP] (My University, 2010)
The common point between the two forms of production of the wood-based sector in Brazil, one practically manufacturing and the other high technology, is in the qualification of the of the labor. In both cases, the professionals are being formed directly in the productive line and rarely with qualification in the academic area. There is not a public political education for the qualification of the labor, and the work market that does not demand qualified professionals, contributes for the sector stagnation. So, in order to excel the socio-cultural barriers in relation to the use of wood in the buildings, new attitudes are necessary in the teaching of the contents of the curricular programs, mainly, in formation of the architect and civil engineering.
Keywords: Education wood; Timber industrial sector; Wood; Civil constructions; Excel; High technology; Industrial sector; Civil engineering; Timber; Civil Engineering; Education; Forests